(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper attempts to describe the life and work of Professor Julka Popović, born Savić (Tübingen 1901 – Belgrade 1985). It tells the story of her parents’ first encounter in Zürich, being born to parents with different nationalities, multicultural and multilingual environment in which she grew up and went to school, specialization in phtysiology, hard times during the war and professional achievements of one of the first women who taught at the Faculty of Medicine, University of Belgrade.